2020
DOI: 10.1590/1980-57642020dn14-030009
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at the epidemiology of schizophrenia and common mental disorders in Brazil

Abstract: ABSTRACT. Schizophrenia and common mental disorders are noteworthy social and economic concern worldwide. Epidemiologic studies on the impact of specific mental disorders in emerging countries are scarce. Objectives: We aimed to characterize the demographic, social, and economic burden of schizophrenia and common mental disorders patients in the health system in Brazil. Methods: Data on these conditions in Brazil between 2008 and 2019 were collected through the website of the Departamento de Informática do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
3
0
11
Order By: Relevance
“…This situation was maintained when analyzing males (increase of 47%) and females (75% increase). Carteri et al (2020) found similar data, studying psychiatric hospitalizations in Brazil, also over a 10-year period. The authors observed a higher prevalence of hospitalizations among women, but described a decrease in hospitalizations during the study period.…”
Section: Discussionsupporting
confidence: 70%
“…This situation was maintained when analyzing males (increase of 47%) and females (75% increase). Carteri et al (2020) found similar data, studying psychiatric hospitalizations in Brazil, also over a 10-year period. The authors observed a higher prevalence of hospitalizations among women, but described a decrease in hospitalizations during the study period.…”
Section: Discussionsupporting
confidence: 70%
“…Nestes estudos, o tempo médio de internação psiquiátrica variou de 22 a 44 dias, a depender da idade, sexo e tipo de transtorno 16,22 . Há a redução no número de dias de internação, e consequentemente nas internações prolongadas 13,16,19,[22][23][24] transtorno por uso e abuso de substâncias. Nesta pesquisa, as meninas permaneciam, em média, mais tempo hospitalizadas que os meninos.…”
Section: Resultsunclassified
“…No que tange a idade média de internação, os estudos revelam que as internações ocorrem sobretudo em indivíduo com idade economicamente ativa, de 29 a 59 anos de idade, sobressaindo-se a terceira década de vida, mas também jovens entre 15 a 29 anos de idade. Os idosos também tem incrementado os dados de internações psiquiátricas, inclusive no que se relaciona ao uso e abuso de substância, especialmente na região norte do país 14,16,18,21,23 inclusive no que se refere aos transtornos relacionado a substâncias 13,14,[16][17][18]20,[22][23][24][25] .…”
Section: Resultsunclassified
“…Atualmente a situação global de hiperexcitabilidade ocasionada pelo rápido fluxo de informações, a alta cobrança e o trabalho excessivo têm contribuído para o aumento da incidência de problemas relacionados à saúde mental, especialmente a depressão, a ansiedade e a Síndrome de Burnout 1,2 . Isso foi percebido especialmente entre as profissões relacionadas ao cuidado e ao servir pessoas em necessidade 3 .…”
Section: Introductionunclassified